2019
DOI: 10.1093/geroni/igz038.660
|View full text |Cite
|
Sign up to set email alerts
|

Online Mindfulness Program for Lonely Older Adults

Abstract: Mindfulness meditation is a cognitive state of self-awareness that promotes emotional regulation and change in self-perspective. Mindfulness has been applied to address loneliness, stress, and anxiety, demonstrating consistent health benefits. The purpose of this study was to test the feasibility of an online mindfulness program and to measure its impact on well-being among lonely older adults. The intervention consisted of seven one-hour weekly online modules led by a trained facilitator via WebEx. Engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Choo et al (2018) reported on the potential use of a smartphone App to deliver mindfulness interventions to older Asian adults at risk for suicide [63]. In another study, Ungar et al (2019) used an online mindfulness program that was greatly beneficial to lonely older adults [64]. The literature exemplifies a growing use of technology to support older adults to "age-in-place. "…”
Section: Discussionmentioning
confidence: 99%
“…Choo et al (2018) reported on the potential use of a smartphone App to deliver mindfulness interventions to older Asian adults at risk for suicide [63]. In another study, Ungar et al (2019) used an online mindfulness program that was greatly beneficial to lonely older adults [64]. The literature exemplifies a growing use of technology to support older adults to "age-in-place. "…”
Section: Discussionmentioning
confidence: 99%